Octreotid Treatment in a Newborn With Congenital Cylothorax - Kurnaz, Erdal; Yakında, Hüseyin; Aslan, Mahmut; Demirtaş, Gülsüm; Özdemir, Ramazan; Karadağ, Ahmet (Fırat University, 2013)
Congenital chylothorax is a rare cause of pleural effusion in the newborn infant. It occurs twice as often in males, and the incidence has been reported as 1/10.000-15.000. There is controversy about the etiology of congenital chylothorax. The diagnosis can be made after analysis of the pleural fluid drained by thoracentesis or chest tube placement. During neonatal period, chylothorax treatment is composed of conservative and surgical therapies. Nowadays, for cases among which conservative therapies fail, treatment with octreotide has been reported to be beneficial with promising results. The prognosis of congenital chylothorax is good but in cases of hydrops fetalis, mortality is increased. A neonate with congenital chylothorax due to hydrops fetalis who was successfully treated with octreotide after failure of autologous blood therapy is presented in this case report.

Konjenital şilotoraks, yenidoğanda plevral efüzyonun nadir görülen bir nedenidir. Erkeklerde sıklığı iki kat fazladır. Görülme sıklığı 1/10.000-15.000'dir. Konjenital şilotoraksın etiyolojisi halen tartışmalıdır. Tanısı plevral efüzyonun tanı ve tedavi amaçlı boşaltılarak analiz edilmesi ile mümkündür. Yenidoğan döneminde şilotoraks tedavisinde konservatif yaklaşımlar cerrahi yöntemler kullanılmaktadır. Günümüzde konservatif yaklaşımlarla sonuç alınamayan olgularda, oktreotid tedavisi ile başarılı sonuçlar alındığı bildirilmektedir. Konjenital şilotoraksın prognozu sıklıkla iyi seyretmekte, ancak hidrops fetalis olgularında mortalite oranı artmaktadır. Bu yazıda ve otolog kan transfüzyonuna yanıt alınamayıp oktreotid ile tedavi edilen, hidrops fetalise bağlı bir konjenital şilotoraks olgusu sunulmuştur.
Konjenital Şilotoraksı Olan Bir Yenidoğanda Oktreotid ile Tedavi